2023
DOI: 10.1007/s00423-023-02814-7
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of predictors for postoperative complications after pancreatectomy––what is new after establishing the definition of postpancreatectomy acute pancreatitis (PPAP)?

Abstract: Purpose We aimed to analyze the predictive value of hyperamylasemia after pancreatectomy for morbidity and for the decision to perform rescue completion pancreatectomy (CP) in a retrospective cohort study. Methods Data were extracted from a retrospective clinical database. Postoperative hyperamylasemia (POH) and postoperative hyperlipasemia (POHL) were defined by values greater than those accepted as the upper limit at our institution on postoperat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…Radulova et al showed a POH1 rate of 52.3% in 437 patients, with soft pancreatic texture and POH on POD1 being independent predictors of POPF. The CR-POPF, major complications (Clavien-Dindo classification > 2), and completion pancreatectomy rates were significantly higher in the POH group [8]. Kuhlbrey et al showed in a retrospective study of 739 consecutive PDs that POD1 systemic hyperamylasemia was a good predictor for CR-POPFs [16].…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Radulova et al showed a POH1 rate of 52.3% in 437 patients, with soft pancreatic texture and POH on POD1 being independent predictors of POPF. The CR-POPF, major complications (Clavien-Dindo classification > 2), and completion pancreatectomy rates were significantly higher in the POH group [8]. Kuhlbrey et al showed in a retrospective study of 739 consecutive PDs that POD1 systemic hyperamylasemia was a good predictor for CR-POPFs [16].…”
Section: Discussionmentioning
confidence: 97%
“…The first attempt at a standard definition of PPAP was made by Connor et al in 2016 who defined PPAP as the elevation of serum amylase levels (hyperamylasemia) above the institutional upper limit of normal on postoperative days (POD) 0 or 1 [6]. Several retrospective studies have found postoperative hyperamylasemia of POD0 or 1 to be significantly associated with a higher rate of POPF [7][8][9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…In a recent study already based on the new ISGPS definition of PPAP, the risk of a rescue complete pancreatectomy in patients after PD was retrospectively assessed. Postoperative hyperamylasemia on POD 1 (regardless of the presence of CR-PPAP) was identified as an independent risk factor of complete pancreatectomy [29]. A reoperation with total pancreatectomy has a high mortality rate but serves as an emergency procedure to deal with potentially fatal complications of PD [44,45].…”
Section: Discussionmentioning
confidence: 99%
“…According to the hypothesis, anastomosis leakage develops as a consequence of necrosis in the pancreatic stump [11,28]. Proper surgical technique, including the use of fine sutures and delicate knotting for the pancreatic anastomosis, is also considered important [29].…”
Section: Discussionmentioning
confidence: 99%